ETHICAL CONSIDERATIONS IN VEDANTA: A SCIENTIFIC APPROACH - Nayak, G C (Journal of Dharma, 1996)
That Ethics and morals have no place in Indian thought, particularly in Vedanta, is a hackneyed criticism against Indian thought. Inspite of the fact that there is ample evidence of emphasis on moral discipline in the Upanisadic writings and writings of Sankard himself, the charge of Indian thought being unethical continues to be there due to a lack of proper understanding of the Indian Philosophical tradition. Such an approach to Indian thought in general and Vedanta in particular is unscientific to the extent to which it is not only not based on adequate evidence but is also based largely on inveterate dogma and prejudice against Eastern, particularly, Indian thought and culture as such.